Optical nanoantennas for multiband surface-enhanced infrared and Raman spectroscopy - D’Andrea, Cristiano; Bochterle, Jörg; Toma, Andrea; Huck, Christian; Neubrech, Frank; Messina, Elena; Fazio, Barbara; Maragò, Onofrio M.; Di Fabrizio, Enzo; Lamy de La Chapelle, Marc; Gucciardi, Pietro G.; Pucci, Annemarie (ACS nano, 2013)
In this article we show that linear nanoantennas can be used as shared substrates for surface-enhanced Raman and infrared spectroscopy (SERS and SEIRS, respectively). This is done by engineering the plasmonic properties of the nanoantennas, so to make them resonant in both the visible (transversal resonance) and the infrared (longitudinal resonance), and by rotating the excitation field polarization to selectively take advantage of each resonance and achieve SERS and SEIRS on the same nanoantennas. As a proof of concept, we have fabricated gold nanoantennas by electron beam lithography on calcium difluoride (1-2 μm long, 60 nm wide, 60 nm high) that exhibit a transverse plasmonic resonance in the visible (640 nm) and a particularly strong longitudinal dipolar resonance in the infrared (tunable in the 1280-3100 cm-1 energy range as a function of the length). SERS and SEIRS detection of methylene blue molecules adsorbed on the nanoantenna’s surface is accomplished, with signal enhancement factors of 5 × 102 for SERS (electromagnetic enhancement) and up to 105 for SEIRS. Notably, we find that the field enhancement provided by the transverse resonance is sufficient to achieve SERS from single nanoantennas. Furthermore, we show that by properly tuning the nanoantenna length the signals of a multitude of vibrational modes can be enhanced with SEIRS. This simple concept of plasmonic nanosensor is highly suitable for integration on lab-on-a-chip schemes for label-free chemical and biomolecular identification with optimized performances.
Gesehen am 04.06.2021